Ethische Aspekte des Alter(n)s im Kontext von Medizin und Gesundheitsversorgung: Problemaufriss und Forschungsperspektiven = Ethical aspects of age(ing) in the context of medicine and healthcare : an outline of central problems and research perspectives - Schweda, Mark; Mitzkat, Anika; Sperling, Uwe; Coors, Michael; Pfaller, Larissa; Rüegger, Heinz; Schmidhuber, Martina; Bozzaro, Claudia (Ethik in der Medizin, 2018)
Definition of the problem: Due to the individual and societal consequences of demographic change, moral questions regarding old age and elderly persons are moving into the focus of public attention and of ethical debates in medicine, nursing and public health. In many of these debates, however, ageing as a process and old age as a phase of life is primarily considered from the angle of the respective practices, questions and problems discussed. What is missing is a perspective that comprises the different practical contexts, makes the underlying conceptions of age(ing) explicit and reflects their meaning for the ethical debate. Arguments: The working group “Ageing and Ethics” in the Academy for Ethics in Medicine was established to contribute to such a more comprehensive perspective. This paper gives an overview of the central topics, problems and arguments in the contemporary medical, nursing and public health ethics discourses on age(ing) and marks open questions and desiderates. Conclusions: A more intensive consideration of age(ing) can not only improve the theoretical basis of the pertaining debates in applied ethics but also shed light on some of the anthropological foundations and normative frameworks of ethical reasoning as such.
Gesehen am 04.09.2019
Online publiziert: 9. Oktober 2017